Improving the Local Economy in Malang Regency Through Optimizing the Potential of Former Indonesian Migrant Workers - Rizal, Mohammad; Mustapita, Arini Fitria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Former Indonesian Migrant Workers in Malang Regency have experience, skills, and global networks. However, many of them face challenges in building sustainable businesses due to limitations in financial management, business insight, and lack of community support and use of digital technology. This condition encourages some of them to return to work abroad due to their inability to develop their businesses independently. Therefore, effective training are urgently needed, with a focus on developing local-based entrepreneurship, simple but applicable financial literacy, and digital marketing strategies. This study aims to evaluate the effectiveness of such training in improving business skills and financial literacy among former migrant workers. This program is designed using the ADDIE model, involving 35 participants from Bantur District, Malang Regency, with the training being implemented in March 2025. Evaluation through pre-test and post-test showed a significant increase in financial literacy and business skills, as reflected in the average pre-test score of 52.29 and an increase in the post-test of 76.57. With a relevant and needs-based approach, this initiative aims to strengthen the local economy in Malang Regency, increase the independence of Former Indonesian Migrant, and encourage their social contribution in building a more empowered community. The training also lays the foundation for sustainable local business growth by equipping participants with practical tools to build, manage, and expand their enterprises.